AN EMPIRICAL STUDY OF CONSUMER’S BEHAVIOR IN RETAIL SECTOR - ANNU KUMARI (International Journal of Multidisciplinary Research and Studies, 2020)
Consumer trends may reveal desires. It shows who buys, why, and how. This evidence is convincing. The results offered remarkable light on how customers' minds work and how those minds alter under different circumstances. Urban consumers' purchasing patterns changed dramatically due to population migrations and increased disposable income. The ever-increasing competition and the availability of various options have helped marketers gain a deeper comprehension of the various factors influencing the demand for hosiery products. This research paper explores why consumers choose certain hosiery products. Family, societal, cultural, and regional variables influence consumers, while their personality, perceptions, and motivation influence them. There are three parts to this process: before a purchase is made, during the decision to buy, and after the item has been acquired. Monthly income, social standing, educational qualification, and brands can influence buying decisions. Cost, packaging, perceived value, cost-benefit analysis, alternative brands etc. may influence the buying choice. Advertising leaves a lasting impression on customers, so marketers must use it to build brand awareness and emotional connections. Brand loyalty is a consumer's ongoing use of the same brand notwithstanding a label change signaling a change in purchasing behaviors. Indian retail has grown rapidly in recent decades. India has conventional and informal retail sectors.